IMPLEMENTASI PENDIDIKAN AGAMA KRISTEN DALAM KELUARGA SEBAGAI UPAYA PEMBENTUKAN IMAN DAN KARAKTER ANAK - Carmelita Ladda; Maria Veronita Skau; Melkiur Olivianus Affi; Regina Tesalonika Banunaek (CV. Adiba Aisha Amira, 2026)
Christian Religious Education (CRE) within the family context holds a crucial role in nurturing children’s faith and shaping their character. The family functions as the primary educational environment that plays a significant role in instilling Christian values through life example, teaching processes, and the habitual practice of faith in daily life. This article aims to analyze the implementation of Christian Religious Education within the family as a means of holistically forming children’s faith and character. The method employed is a literature review using a descriptive–qualitative approach based on relevant theological, pedagogical, and psychological sources. The findings indicate that the effectiveness of CRE implementation in the family is determined by the active involvement of parents as faith educators, the application of values such as love, discipline, and responsibility, and consistent spiritual formation through prayer and Bible reading. Christian Religious Education in the family not only serves as a means of transmitting faith knowledge but also functions as a continuous process of shaping Christian character. Therefore, family-based CRE becomes a strategic means of preparing children to develop mature faith and character that reflect the values of Christ in their daily lives.